2018
DOI: 10.1097/pep.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Arm Bimanual Intensive Therapy Improves Prefrontal Cortex Activation in Children With Hemiplegic Cerebral Palsy

Abstract: HABIT potentially improves the PFC's involvement in the action planning of the upper extremity movements in children with HCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Higher activation in unilateral CP can therefore be related to the greater effort needed to produce a coordinated asymmetric movement against the tendency to produce more symmetric movements . Finally, asymmetric tasks may increase attentional demands, as suggested by an earlier study on complex action planning in children with unilateral CP that demonstrated greater prefrontal cortical activation compared with controls . Our findings in the sensorimotor cortex may therefore indicate increased need for sensorimotor resources to perform complex motor tasks.…”
Section: Discussionsupporting
confidence: 53%
“…Higher activation in unilateral CP can therefore be related to the greater effort needed to produce a coordinated asymmetric movement against the tendency to produce more symmetric movements . Finally, asymmetric tasks may increase attentional demands, as suggested by an earlier study on complex action planning in children with unilateral CP that demonstrated greater prefrontal cortical activation compared with controls . Our findings in the sensorimotor cortex may therefore indicate increased need for sensorimotor resources to perform complex motor tasks.…”
Section: Discussionsupporting
confidence: 53%
“…Rather the motor decisions seen in these children are also partly dependent upon how they process and perceive visual information. This view fuels the emerging perspective that the abnormal motor actions seen in children with CP are fundamentally influenced by top-down processing (Gordon, 2016; Kurz et al, 2017a; Lust et al, 2018; Surkar et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…8 However, the functional basis of these improvements remains poorly understood, as the neuroimaging literature has predominantly focused on identifying how structural aberrations (eg, fiber track integrity) modulate the clinically relevant improvements seen after these interventions, [9][10][11] with very few studies examining neural activity within the key networks that serve the production of the hand motor actions. [12][13][14][15] The outcomes from functional MRI (fMRI) have noted that children with CP have reduced sensorimotor cortical activity in the hemisphere contralateral to the more affected hand, and compensatory cortical activity in the ipsilateral hemisphere. 14,[16][17][18] Resting-state analyses have also shown less connectivity in the sensorimotor cortices of the more affected hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, the functional basis of these improvements remains poorly understood, as the neuroimaging literature has predominantly focused on identifying how structural aberrations (eg, fiber track integrity) modulate the clinically relevant improvements seen after these interventions, 9-11 with very few studies examining neural activity within the key networks that serve the production of the hand motor actions. 12-15…”
Section: Introductionmentioning
confidence: 99%